Appetitive Olfactory Learning and Long-Term Associative Memory in Caenorhabditis elegans - Nishijima, Saori; Maruyama, Ichiro N. (Frontiers in Behavioral Neuroscience, 2017)
Because of the relative simplicity of its nervous system, Caenorhabditis elegans is a useful model organism to study learning and memory at cellular and molecular levels. For appetitive conditioning in C. elegans, food has exclusively been used as an unconditioned stimulus (US). It may be difficult to analyze neuronal circuits for associative memory since food is a multimodal combination of olfactory, gustatory and mechanical stimuli. Here we report classical appetitive conditioning and associative memory in C. elegans, using 1-nonanol as a conditioned stimulus (CS), and potassium chloride (KCl) as a US. Before conditioning, C. elegans innately avoided 1-nonanol, an aversive olfactory stimulus, and was attracted by KCl, an appetitive gustatory stimulus, on assay agar plates. Both massed training without an intertrial interval (ITI) and spaced training with a 10-min ITI induced significant levels of memory of association regarding the two chemicals. Memory induced by massed training decayed within 6 h, while that induced by spaced training was retained for more than 6 h. Animals treated with inhibitors of transcription or translation formed the memory induced by spaced training less efficiently than untreated animals, whereas the memory induced by massed training was not significantly affected by such treatments. By definition, therefore, memories induced by massed training and spaced training are classified as short-term memory (STM) and long-term memory (LTM), respectively. When animals conditioned by spaced training were exposed to 1-nonanol alone, their learning index was lower than that of untreated animals, suggesting that extinction learning occurs in C. elegans. In support of these results, C. elegans mutants defective in nmr-1, encoding an NMDA receptor subunit, formed both STM and LTM less efficiently than wild-type animals, while mutations in crh-1, encoding a ubiquitous transcription factor CREB required for memory consolidation, affected LTM, but not STM. The paradigm established in the present study should allow us to elucidate neuronal circuit plasticity for appetitive learning and memory in C. elegans. □